Navigation and Waterpower : Adaptation and Technology on Canadian Canals - Desjardins, Pauline (The Journal of the Society for Industrial Archeology, 2003)
Number: 1
Keywords: Navigation; Énergie hydraulique

Steamboat connections : Montreal to Upper Canada, 1816-1843 - Mackey, Frank (McGill-Queen's University Press, 2000)
"In Steamboat Connections Frank Mackey gives us a narrative account of the first twenty-five years of steam navigation along the St. Lawrence and Ottawa Rivers. Relying on a wealth of primary archival sources, Mackey focuses on the development of steamer traffic from 1816 - when the foundations were laid for the first stage and steamboat line between Montreal and Upper Canada - to the early 1840s - when locks, canals, innovations, and human daring conquered the rapids on those rivers and allowed for navigation between Montreal and the Great Lakes. He shows how, starting in 1841, small steamers ran "the circuit" - down the rapids of the St. Lawrence to Montreal and then back up to Kingston and other Great Lakes ports via the Ottawa River and the Rideau Canal." "Mackey introduces the entrepreneurs who forged this important link between Montreal and the nation's interior and chronicles the course of their industry, correcting previous misinterpretations. He sheds light not only on steamboats but also on the social, commercial, and geographical development they made possible. He shows that the history of this country, a land with vast expanses and a harsh climate, cannot be fully appreciated without looking at the different modes of transportation that made it possible."–BOOK JACKET.
Keywords: Navigation

“The Severity of This Service…” Canadien Inland Mariners in the Early Post-Conquest Era, 1760 to 1817 - More, John David (Université Queen's, 2021)
Keywords: Guerre; Navigation

Le Saint-Laurent, comme une rue principale - Franck, Alain (Continuité, 2001)
issued: 2001-22-00
Keywords: Navigation; Voie maritime

Au canal de Lachine - Desjardins, Pauline (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Lachine (canal); Navigation

La rivière des Prairies - Dupont, Antonin (Il était une fois... Montréal-Nord, 2002)
issued: 2002-22-00
Keywords: Navigation; Rivière des Prairies

Une artère vitale: le fleuve - Gelly, Alain (Cap-aux-Diamants, 2012)
issued: 2012-23-00
Keywords: Chemins de fer; Navigation; Routes

En rade: marins à Montréal (1851-1896) - Bélisle-Desmeules, David (Leméac, 2019)
Keywords: Navigation; Port; Travail; Vieux-port

La Babylone des marins : Marins hauturiers à Montréal 1851-1896 - Bélisle-Desmeules, David (Université de Montréal, 2016)
Keywords: Alcool; Navigation; Port; Taverne Joe Beef

" Du chemin qui marche " au chemin du Roy à la Pointe-aux-Trembles - Desjardins, Pierre (Histoire Québec, 2010)
Number: 2
Keywords: Navigation; Pointe-aux-Trembles; Routes; Voirie

La compagnie maritime Allan: de l'Écosse au Canada au XIXe siècle - Blondel-Loisel, Annie (L'Harmattan, 2009)
Keywords: Allan Royal Mail Line; Allan; Andrew; Allan; Hugh; Navigation

Voies pointelières d'hier et d'aujourd'hui - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2006)
Keywords: Chemins de fer; Navigation; Pointe-aux-Trembles; Quartiers